Development of Rempah Kita illustrated book to introduce spice diversity to children aged 7–12 - Cahyani, Wiwit; Setiaji, Rony Siswo (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2024)
This study aims to describe the process of development and material feasibility as well as the feasibility of the picture book media "Rempah Kita". This study used the Brog and Gall R&D method. The stages that are carried out consist of potential problems, data collection, product design, validation, product design improvement, and product trials. This study was conducted on children aged 7–12 at SD Negeri Sedangsari. Research data collection using observation techniques, interviews, questionnaires and documentation. Data analysis techniques are quantitative and qualitative descriptive.  This research and development results are as follows: (1) The picture storybook "Rempah Kita" for children aged 7–12 years is equipped with a Game Card. The story's content is divided into two parts, equipped with the values of character education and love for the motherland. (2) The feasibility results of the picture storybook "Rempah Kita" based on the assessment of material experts get a response score of 90%, while the results of trials for children aged 7–12 years for material quality get a response score of 95%. (3) The feasibility results of the picture storybook "Rempah Kita" based on the assessment of media experts received a response score of 85%, while the results of trials for children aged 7–12 years for media quality received a response score of 96.75%. Thus, the picture storybook "Rempah Kita" gets a very decent category (SL) regarding material and media.